2004
DOI: 10.1191/0269216304pm933oa
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive mechanical ventilation as a palliative treatment of acute respiratory failure in patients with end-stage solid cancer

Abstract: Noninvasive ventilation (NIV) is widely used in the treatment of acute respiratory failure (ARF), but not in patients with end-stage solid cancer in whom any form of mechanical ventilation tends to be avoided. In a prospective study, we investigated the use of NIV in 23 patients with solid malignancies receiving palliative care and who were affected by severe hypoxic or hypercapnic ARF. The most frequent causes of ARF were exacerbations of pre-existing pulmonary diseases and pneumonia. After one hour, NIV sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 37 publications
2
39
1
13
Order By: Relevance
“…14 In one particular study of noninvasive ventilation in oncologic patients, 13 of 23 (57%) patients were successfully supported and discharged alive. 28 In the present study, the mortality rate was 55% for noninvasive mechanical ventilation group; however, when this group was compared with those who did not have noninvasive mechanical ventilation, statistical significance was not reached after adjusting for known confounding factors. The role of early noninvasive mechanical ventilation merits further research.…”
Section: Duringcontrasting
confidence: 59%
“…14 In one particular study of noninvasive ventilation in oncologic patients, 13 of 23 (57%) patients were successfully supported and discharged alive. 28 In the present study, the mortality rate was 55% for noninvasive mechanical ventilation group; however, when this group was compared with those who did not have noninvasive mechanical ventilation, statistical significance was not reached after adjusting for known confounding factors. The role of early noninvasive mechanical ventilation merits further research.…”
Section: Duringcontrasting
confidence: 59%
“…Concerning the use of NIV as a "sole" palliative measure to relieve dyspnea, 60 a recent RCT 61 found that in end-stage solid cancer patients, NIV improved dyspnea faster than did oxygen alone, and reduced the amount of morphine needed.…”
Section: Niv In Patients With Do-not-intubate Orders and For Symptom mentioning
confidence: 99%
“…NPPV reduces dyspnoea even in the absence of hypercapnic respiratory failure [110]. The Society of Critical Care Medicine has recently charged a task force with the development of an approach for considering use of NPPV in patients who choose to forgo endotracheal intubation.…”
Section: Nppv In Palliative Carementioning
confidence: 99%